A case of lethal spontaneous massive hemothorax in a patient with neurofibromatosis 1 - Zacarias Föhrding, Luisa (J Cardiothorac Surg, 2014)
Neurofibromatosis type 1 is an autosomal dominant disease characterized by multiple dermatological disorders amongst others. Among the less frequent manifestations are vascular abnormalities. Here, we present a case of spontaneous massive hemothorax in a 39-year-old Caucasian woman with neurofibromatosis 1 and a thoracic meningocele with a lethal outcome despite extensive surgical intervention as well as intensive care measures. Spontaneous hemothorax is a rare, but potentially lethal complication of neurofibromatosis type 1, which necessitates quick and decisive intervention; endovascular embolization where possible, otherwise aggressive surgical intervention in unstable patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13019-014-0172-y) contains supplementary material, which is available to authorized users.